PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TENTANG MATERI SHALAT UNTUK SISWAKELAS IV SDN 26 NANGGALO TARUSAN KABUPATEN PESISIR SELATAN - Darneti Darneti (IICET (Indonesian Institute for Counseling, Education and Therapy), 2016)
Advancement in the education field requires teacher to make use of technology and science in learning process. Subject of Islamic study at SDN 26 Nanggalo Tarusan Pesisir Selatan has no learning media such as video showing material of Shalat yet. This learning media lets students be motivated and understand the material easily. This research is a development research using model of 4D (define, design, develop, disseminate) but it does not include the stage of disseminate. Stage of define includes curriculum, student, and media analysis. Stage of design includes design the learning media of video. Stage of develop includes validity test by validator and practicality test by student of grade IV SDN 26 Nanggalo Tarusan Pesisir Selatan. This research obtains a practical product in form of video showing material Shalat as learning media for Islamic study subject.